(untitled) (Eurasian Scientific Herald, 2022)
The review article highlights the scientific works of foreign scientists on metabolic, immunological causes and pathological mechanisms of osteoarthritis, which is becoming younger and an urgent problem among arthrolgic diseases in the elderly, leading to early disability and increasing economic problems.